Measuring corporate brand equity of Universiti Sains Malaysia (USM) - Md Noor, Shuhaida; Abdul Manan, Kamaruzzaman; Abdul Kuthoos, Haja Mydin (2018)
Corporate brand equity studies focus heavily on brands of profit-based organisations. Similarly in Malaysia, while there has been a number of studies on leading brands owned by profit-based such as PETRONAS, Air Asia and Maxis, there has been a dearth of studies on brands of not-for-profit organisations such as public universities. Public university brands tend not to place a high priority on brand development due to the lack of understanding on the significance of corporate brand equity. The increasing pressure for public universities to compete in the highly competitive higher education market is slowly changing this perception. Therefore, this study will offer some preliminary insights into the dimensions contributing to the corporate brand equity of a public university in Malaysia. The study was conducted as part of the effort in understanding the corporate brand equity of Universiti Sains Malaysia and provides an understanding on the use of metrics in assessing a university brand and be a point of departure in developing a corporate brand equity metrics for higher education institutions. Data collection was conducted using survey method by distributing questionnaires to 400 students from eight local public universities. The findings of this study indicate that the dimensions of awareness, quality of the service, trust and relevance have a positive relationship with USM corporate brand equity. The findings may guide future researchers in the understanding of the dimensions contributing to the corporate brand equity of public universities.